Hearing Health in Agricultural Aviation Pilots from Cindacta II Wearing Earplugs and a Helmet - Fonseca,Vinicius Ribas (2016)
Abstract Introduction Agricultural aviation pilots, exposed daily to intense vibration and noise, are likely to develop noise-induced hearing loss (NIHL). Objectives The aim of this study was to investigate the presence of audiograms consistent with NIHL in agricultural aviation pilots who use earplugs and helmets. Methods We conducted a cross-sectional cohort and observational study. The data were taken from the medical records and audiograms of 94 pilots. Results NIHL was identified in 9.5% of individuals with hearing loss by audiograms at 3,000, 4,000, or 6,000 Hz. Normal audiograms were observed in 46.8% of pilots surveyed. Bilateral hearing loss was more frequent than unilateral hearing loss, occurring in 64.8% of cases. Conclusion Although there was a low incidence of audiograms compatible with NIHL in the records of the pilots examined, the disorder still occurs despite the doubled use of individual hearing protection equipment (helmets and earplugs) for agricultural aviation pilots. Nevertheless, even with the use of earplugs and helmets as noise protectors, the data showed that agricultural pilots suffer inner ear damage caused by occupational noise. Prevention and periodic audiologic evaluations must be conducted in noiseexposed occupational groups.